Exploring the Research on Utilizing Machine Learning in E-Learning Systems - Harfizar; Edian Martin; Muhamad Abdul Aziz; Allif Pujihanarko; Noviesta Riani Pratiwi (Pandawan Sejahtera Indonesia, 2023)
Naturally, you are already familiar with the phrase